High Unemployment in Germany: Why do Foreigners Suffer Most? - Wido Geis (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
In Germany, immigrant unemployment is not only higher than native unemployment; italso reacts more to changes in the situation on the labor market. Decomposing the gapbetween native and immigrant unemployment into a baseline and a labor-marketsituation component, I find that the unemployment rate of immigrants would lie at 5.6 percentagepoints for zero native unemployment (the baseline component of the gap). Anincrease in overall unemployment by 1 percentage point leads to a 0.7 percentage pointshigher increase in immigrant unemployment than in native unemployment (the situationcomponent). The large part of this difference, about 3/4 of the baseline and 4/5 of thesituation component, can be explained by differences in the endowments with classicalhuman capital (educational degrees and experience) between immigrants and natives.Also controlling for country-specific human capital, particularly language skills, thesituation component becomes insignificant and the baseline effect again decreases by1/2. Adding controls for social networks, the baseline effect also becomes insignificant.Thus, human capital and social networks can possibly fully explain the differencebetween native and immigrant unemployment in Germany.
Keywords: F22; J24; J61; J64; J71; 330; Immigration; integration; unemployment; human capital; language skills; discrimination; social networks; Migranten; Arbeitslosigkeit; Bevölkerung; Humankapital; Soziales Netzwerk; Deutschland